IMPACT OF MACROECONOMIC FACTORS ON THE BANKING SECTOR IN UZBEKISTAN (Academia Science Repository, 2023)
This article covers the prospects of the countries of Uzbekistan and Kazakhstan in the framework of cooperation relations in recent years and how important they are in inter-state relations.